The Shrinking Resource Base of Pastoralism: Saami Reindeer Husbandry in a Climate of Change - Tyler, Nicholas J. C.; Hanssen-Bauer, Inger; Førland, Eirik J.; Nellemann, Christian (Frontiers in Sustainable Food Systems, 2021)
The productive performance of large ungulates in extensive pastoral grazing systems is modulated simultaneously by the effects of climate change and human intervention independent of climate change. The latter includes the expansion of private, civil and military activity and infrastructure and the erosion of land rights. We used Saami reindeer husbandry in Norway as a model in which to examine trends in, and to compare the influence of, both effects on a pastoral grazing system. Downscaled projections of mean annual temperature over the principal winter pasture area (Finnmarksvidda) closely matched empirical observations across 34 years to 2018. The area, therefore, is not only warming but seems likely to continue to warmdo so. Warming notwithstanding, 50Fifty-year (1969-2018) records of local weather (temperature, precipitation and characteristics of the snowpack) nevertheless demonstrate considerable annual and decadal variation which also seems likely to continue and alternately to amplify and to counter net warming. Warming, moreover, has both positive and negative effects on ecosystem services that influence reindeer. The effects of climate change on reindeer pastoralism are evidently neither temporally nor spatially uniform, nor indeed is the role of climate change as a driver of change in pastoralism even clear. The effects of human intervention on the system, by contrast, are clear and largely negative. Gradual liberalisation of grazing rights from the 18th Century has been countered by extensive loss of reindeer pasture. Access to approximately 50% of traditional winter pasture was lost in the last19th century owing to the closure of international borders to the passage of herders and their reindeer. At the same timeSubsequent this the area of undisturbed pasture within Norway has decreased by 71%. Loss of pasture from piecemeal development of infrastructure and administrative encroachment that erodes herders’ freedom of action on the land that remains to them are the principal threats to reindeer husbandry in Norway today. These tangible effects far exceed the putative effects of current climate change on the system. The situation confronting Saami reindeer pastoralism is not unique: loss of pasture and administrative, economic, legal and social constraints bedevil extensive pastoral grazing systems across the globe.